The spatial effects of agricultural tenure in Wasit Governorate and its relationship to the population (Journal of the College of Basic Education, 2023)
The size of the holding affects the characteristics of agricultural production. Large holdings are cultivated with grains such as wheatBarley and the purpose of production is commercial as in. Lands of the island in terms of Azizia for whatSmall-sized holdings, so it is cultivated with fruits and peels, as is 7 in holdings close to a riverDijla, as well as the size of the holding has an impact on the population density. In lands that decrease, the size of the holding increasesThe population is more mule than the population in the areas where the size of the possession expands, and that is due to the age of the researchThe inventory of services such as schools and hospitals with large holdings and the prevalence of the phenomenon of population unemployment also appearedThe large holdings use machines and machines, and the tamping system is common in them, in contrast to the holdingsThe small scale in which manual work is widespread with the use of the agricultural cycle.